A row of Shiva Lingas near the Ghateshwar Temple - Temples of India Project Team (Jio Institute, 2024)
A row of Shiva lingas can be seen near the Ghateshwar Temple. There are seven Shiva lingas placed on plain pedestals. According to the temple priest, these Shiva lingas were set up by the families of the earlier priests after their deaths, and they are said to be their samadhis (memorial shrines).